DESIGN AND FABRICATION OF SMALL SCALE SUGARCANE HARVESTER - .Masute, Mr. Rohit J; Chaudhari, Dr. Sharad S.; Khedkar, Prof .S. S. (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
This project aims to design and fabricate small scale sugarcane harvesting machine for sugarcane harvesting to reduce farmer’s effort and to increase production of agricultural products. Machine consists of petrol engine and different mechanisms are used in this machine. When compare to manual harvesting by using this machine has a capacity to cut canes in faster rate and it is economical. The machine is helpful for both whom having small or big farms